A review of current evidence for vilazodone in major depressive disorder. (August 2013) - Wang, Sheng-Min; Han, Changsu; Lee, Soo-Jung; Patkar, Ashwin A.; Masand, Prakash S.; Pae, Chi-Un
Abstract: Objectives. This review is to inform clinicians of currently available data on vilazodone for treating patients with major depressive disorder (MDD), focusing on its differential action mechanism and extended clinical utility. Methods. A data search was conducted in June 2012 using the PubMed/ MEDLINE/relevant clinical trial databases with the key terms "vilazodone" or "Viibryd." Results. The efficacy, safety, and tolerability of vilazodone have been demonstrated in two pivotal 8-week, randomized, double-blinded, placebo-controlled studies. Certain pharmacological characteristics of vilazodone were observed, including early onset of action, fewer sexual side effects, the absence of known cardiac toxicity, and minimal effect on weight gain, that may provide potential clinical advantages compared with currently available antidepressants. However, such possibilities should be replicated and confirmed in more well-designed and adequately powered clinical trials. Vilazodone requires dose titration up to 2 weeks to reach a target dose of 40 mg/d due to high rate of gastrointestinal side effects. No direct comparative studies with other antidepressants are currently available to confirm the aforementioned potential clinical utility. Conclusion. Vilazodone is a newer antidepressant possessing different action mechanisms compared to currently available antidepressants but whether it has superiority to other class of antidepressants in terms of efficacy and safety should still warrant further evaluation through more well-controlled and direct comparison clinical trials.